Analisis Kepemimpinan Pemerintah Kabupaten Sidenreng Rappang Dari Aspek Ekonomi, Sosial dan Politik - Barisan Barisan; Zuly Qodir (Journal of Governance and Public Policy, 2016)
This research to intend for the describe and analyze about the political participation a minority communities by takingthe case on Towani Tolotang in Sidenreng Rappang. The method used in this research is descriptive qualitative andanalysis is done through collection, reduction, and categorizing. The result showed that political participation TowaniTolotang high at 64.3 % Towani Tolotang high political participation can not be separated from the strong relationshipthat woke persuasive in the group through activities Tudang Sipulung (seated together). The participation aims tobuild a network/political connection to the government in order to maintain its existence. Tolotang Towani behavior inchoosing a traditional-critical. Traditional form that they always choose the candidate who comes from the group, whilethe critical Hape that they see the private candidates before settling on the choice. The factors that influences the highparticipation that is the compromise between Towani Tolotang with the government. The form of compromise that is allthe government did not prohibit their customary activities and the government also does not deviate from the NKRIthen along the Towani Tolotang always believe and support the government.